Analisis Quality of Service (QoS) Jaringan Internet Pada Admin Building PT. Semen Baturaja (Persero) Tbk. Berbasis Wireshark - Muhamad Ridho Marza; Safaruddin Safaruddin; Achmad Azhari (Publikasi Indonesia, 2022)
This study discusses the QoS (Quality of Service) Analysis of the Internet Network in the admin building of PT. Semen Baturaja. Quality of Service is a method of measuring how good the network is and is an attempt to define the characteristics and properties of a service. Referring to the construction of internet services in the admin building of PT. Semen Baturaja, it is necessary to research the measurement of QoS (Quality of Service) of the internet network in the admin building of PT. Semen Baturaja.Measurements of QoS parameters such as Delay, Jitter, Packet Loss and Throuhgput were carried out on the 1st floor at 08.00 WIB, 12.00 WIB and 16.00 WIB using the Wireshark application. average delay is 20,695 ms with index 4 and category